2015
DOI: 10.1021/acs.est.5b00205
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of BrCl, Br2, BrOCl, Br2O, and HOBr to Regiospecific Bromination Rates of Anisole and Bromoanisoles in Aqueous Solution

Abstract: When bromide-containing waters are chlorinated, conventional wisdom typically assumes HOBr is the only active brominating agent. Several additional and often-overlooked brominating agents (including BrCl, Br2, BrOCl, Br2O) can form in chlorinated waters, albeit at generally lower concentrations than HOBr. The extent to which these additional brominating agents influence bromination rates of disinfection byproduct precursors is, however, poorly understood. Herein, the influence of BrCl, Br2, BrOCl, Br2O, and HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 47 publications
7
56
0
Order By: Relevance
“…Accordingly, the HOF molecule can undergo electrophilic addition with olefin [ 55 ]. Notably, a large number of studies have shown that the HOBr molecule is not a good brominating agent in water treatment compared to Br 2 and Br 2 O [ 56 ], which is also consistent with our computations.…”
Section: Resultssupporting
confidence: 91%
“…Accordingly, the HOF molecule can undergo electrophilic addition with olefin [ 55 ]. Notably, a large number of studies have shown that the HOBr molecule is not a good brominating agent in water treatment compared to Br 2 and Br 2 O [ 56 ], which is also consistent with our computations.…”
Section: Resultssupporting
confidence: 91%
“…HOCl and NH 2 Cl quickly oxidize Br – and I – to produce other electrophilic halogen species (e.g., HOBr and HOI). , Researchers examining electrophilic substitution often focus on reactions directly involving the most abundant halogen species [e.g., hypohalous acids (HOX), where X = Cl, Br, or I]. , However, reaction models that include only the electrophiles that are prevalent in chlor­(am)­inated water sometimes fail to accurately predict product distributions and the effects of halide ion concentration, disinfectant concentration, and pH on reaction rates (see examples in Figures S1–S3). …”
Section: Introductionmentioning
confidence: 99%
“…The [(H 2 O)(opbmz) 2 Fe‐OOH] formed in the case of oxidative bromination would later react with Br − ion to liberate HOBr that may bind to the Fe center and attack the substrate by an electrophilic attack (Br + ) to give bromo‐product …”
Section: Resultsmentioning
confidence: 99%